Sosialisasi Penguatan Ekonomi Masyarakat Melalui Pendidikan Kewirausahaan di Desa Firdaus - Yomeini Margareth Sagala; Suci Etri Jayanti; Daniel Collyn; Rapat Piter Sony Hutauruk; Rika Surianto Zalukhu; Yenni Mariani Sinurat; Rodi Syafrizal; Ayu Zurlaini Damanik; Suwadi Suwadi; Bobby Hartanto; Kumala Vera Dewi; Cici Puspaningrum; Murbanto Sinaga (Lembaga Pengembangan Kinerja Dosen, 2024)
The ratio of entrepreneurs in Firdaus village, Sei Rampah District, Serdang Bedagai Regency, is considered very low. This low ratio is attributed to the community's low interest in entrepreneurship. Most of the community believes that entrepreneurship requires a large amount of capital. Additionally, there are risks that may occur, such as losses and uncertainty regarding income. Therefore, a community service activity in the form of socialization was conducted for the people of Firdaus village. This socialization activity aimed to provide entrepreneurship education to the community in Firdaus village, thus fostering interest in entrepreneurship. The socialization activity was attended by 22 participants. The methods used in this community service activity were lectures and interactive discussions. The stages of the community service activities included the preparation stage and the implementation stage. This activity had a positive impact on increasing the knowledge of the participants regarding the entrepreneurial skills that an entrepreneur must master, as well as the importance of marketing strategies and the use of technology in the success of a business. Several participants expressed interest in entrepreneurship after participating in the community service activity. This indicates that the community service activity has made a positive contribution to the people of Firdaus village.